Estudo da prevalência da alergia ao níquel através de teste cutâneo em crianças de 5-12 anos - Torrel, Bruna (2017)
Nickel is related to contact allergy prevalently in the population. The etiological factors of the development of the sensitivity to the metal are investigated in several researches and its knowledge becomes necessary, since the Dentistry has several materials that have nickel in its composition. Thus, the objective of our study was to identify the prevalence of nickel sensitivity by skin test in children aged 5-12 years. The sample consisted of 87 individuals, who were screened for dental care at the Odontopediatrics Clinics I and II of the Dentistry Course of the Federal University of Santa Maria. The results of the study revealed that 42.5% of the individuals reacted positively to the nickel sensitivity skin test. In the distribution of the sample regarding sex the results demonstrated the presence of sensitization to nickel in 32.4% of males and 67.6% of females. We can conclude that the cutaneous sensitivity to nickel has a high prevalence (42.4%) considering the age range of 5-12 years, being higher in females.